The Effect Of Work Motivation And Compensation On Employee Performance At Company XYZ - Rizkya Dewi, Tsaniya Nurul; Luturlean, Bachruddin Saleh (SEAN Institute, 2025)
Currently infrastructure companies are growing rapidly. However, at PT. XYZ experienced a decrease in gross profit which caused a loss. This is of course related to its Human Resources (HR), therefore companies really need quality and good and responsible Human Resources (HR), as they are inseparable to the factors driving employee motivation and the rewards offered to employees, both of which determine their performance. The present study strives to identify how work motivation and compensation impact employee performance at PT XYZ. This investigation employs a quantitative research, specifically a descriptive type. The target population consists of all employees at XYZ company, which totaled 200 employees. The saturation technique is used to select the sample, encompassing the entire population taken, namely a total of 200 employees. The obtained data is subsequently analyzed employing the SPSS software. The analytical procedures performed include data transformation with MSI, classic assumption testing, hypothesis testing, and determination coefficient analysis. The findings state that Work Motivation (X1) remarkably impacts Employee Performance (Y), Compensation (X2) remarkably impacts Employee Performance (Y), whereas Work Motivation and Compensation have a combined impact on the level of Employee Performance (Y).